PUSAT PENELITIAN BIOTEKNOLOGI-LIPI, JL. RAYA BOGOR KM. 46, CIBINONG, 16911, JAWA BARAT, INDONESIA - Susetio, Muhammad; Efendi, Darda; Sari, Laela (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACTBentul taro (Colocasia esculenta) is one of taro cultivar which has high productivity. Genetic improvement has been done by obtaining tetraploid taro. Drought tolerant cultivars can be achieved by addition of poly ethylene glycol (PEG) in vitro. The purpose of this study was to determine the effect of the treatment of PEG concentrations on in vitro growth of tetraploid shoots and to propagate shoots after PEG treatment. The explants used were diploid taro shoots, tetraploid clones 2.1.2 and 2.4.2. Shoots were planted in MS media without PEG and with PEG of 5, 10 and 15%. The growth parameters observed were petiole length, number of leaves, and number of roots every week for 6 weeks. Proline content and LC50 values were analyzed at 6 weeks after planting. Propagation of shoots after PEG treatment was carried out on MS media containing 2 mg / L BAP, 1 mg / L thiamine, and 2 mg / L adenine. Each treatment consisted of 15 shoots as replicates. The growth parameters observed were petiole length, number of leaves, and number of shoots every week for 6 weeks. The results showed that Bentul taro clones significantly affected the concentration of PEG on growth parameters. LC50 value of diploid clone was 12.16%, clone 2.1.2 was 13.54%, and clone 2.4.2 was 12.74%. The highest proline content was found at Bentul tetraploid clone 2.1.2. After PEG treatment, growth was significantly affected by PEG concentrations. All Bentul taro clones after PEG treatment produced multiple shoots.  Keywords: Taro (Colocasia esculenta), in vitro selection, diploid, tetraploid, proline, LC50, propagation